Pharmacokinetics of a new imidazoline receptor agonist in rat plasma after intragastric and intravenous administration - Kulikov Aleksandr,Avtina Tatyana,Pokrovsky Mikhail,Korokin Mikhail (Journal of Applied Pharmaceutical Science, 2017)
3-(1h-benzimidazol-2-yl)-1,2,2- trimethylcyclopentancarboxylic acid (C7070) is a novel synthetic imidazoline receptor agonist - potential antidiabetic agent. This study aimed to obtain the pharmacokinetic profiles in rats. Additionally, an HPLC MS/MS method was developed and validated to quantify C7070 in rat plasma. The pharmacokinetic profiles of intragastric and intravenous administration routes at singles doses of 50 mg/kg, were studied in rats. The elimination half-life of intravenously administered C7070 was approximately 154.1 min. The maximum plasma level of C7070 was reached approximately 170 min (2.8 h) after intragastric administration, with a Cmax value of 17.6 μg/mL and an AUC (o-t) value of 6964 μg*min-1/mL; the oral bioavailability was approximately 18%.
Keywords: New antidiabetic agent, HPLC MS/MS, Pharmacokinetics, Imidazoline receptor agonist, C7070, Rat.